MEMBANGUN KUALITAS LAYANAN, KUALITAS PRODUK, DAN PERSEPSI HARGA UNTUK MENDUKUNG WORD OF MOUTH MELALUI KEPUASAN - Rendy Aji Widodo Candra; Muchsin Shihab Saggaff (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
This study aims to analyze the effect of service quality, product quality and perceived price on customer satisfaction and the implications on WOM. This research is descriptive-quantitative in nature. Secondary data were gathered from various sources such as books and journals and other related publications. Primary data were obtained using questionnaire distributed to Indihome customers in Jakarta city. Using a purposive sampling technique, a total sample of 120 Indihome customers was obtained. Data were analyzed using Path analysis. Various statistical tests such as validity, reliability, normality tests were also employed. The results showed that the service quality, product quality and perceived price partially and simultaneously had a significant and positive effect on customer satisfaction. Furthermore, only the variables of product quality and perceived price were found to have a direct effect on WOM. Customer satisfaction as an intervening variable had a significant effect on WOM. Since the variables are multi-dimensional, it is recommended that the company pay attentions onthe dimensions of the variables being observed.